Expert perspective on health and safety determinants in wineries. - Anaya-Aguilar, Carmen; Suárez-Cebador, Manuel; Rubio-Romero, Juan Carlos; Anaya-Aguilar, Rosa María (IOS Press, 2022)
BACKGROUND: The scientific literature contextualizes health and safety (H&S) in two major models, the first is based on a holistic perspective with H&S processes in all company departments, and the second approaches health and safety management from a more operational perspective. In this study, we examine the issue of health and safety in wineries. In 2017, a census showed that wineries account for 14% of the food and beverage industry in Spain. They provide direct employment for 24,051 people and involve complex winemaking processes that can cause accidents or occupational diseases. Wineries are part of the industrial sector, which, with 5,264 lost-time accidents per 100,000 workers in 2017, ranks second in the number of occupational accidents in Spain. This shows the need to determine the changes needed to improve health and safety in wineries. METHODS: In this study, we identify H&S determinants in wineries using Delphi methodology with a panel of 11 experts. CONCLUSION: The experts gave high scores to the “activities” dimension, and others such as “control of personal and collective protective equipment” and “training”, together with “accident investigation“, “coordinated health and safety mea sures” and “signage” are associated with operational health and safety determinants, namely, capitalizing on knowledge gained in situ and promoting organizational
https://v2.sherpa.ac.uk/id/publication/2067
Keywords: Bodegas (Empresas); Seguridad industrial; Seguridad e higiene laboral; Accidentes de trabajo; Occupational accidents; Wineries; Risk assessment; Safety; Health